2019
DOI: 10.1111/jocn.15086
|View full text |Cite
|
Sign up to set email alerts
|

“It’s got its own life, and you can’t contain it”: A qualitative study of patient and health professional experiences of diabetes care

Abstract: Aims and objectives To explore the perspectives of patients and health professionals on facilitators and barriers to care in a diabetes clinic in urban South Africa. Background Although much attention has been given to the science behind diabetes management, a qualitative approach to exploring experiences, facilitators and barriers to care may have considerable value in understanding and improving diabetes care. Design We conducted a qualitative study in the context of a 3‐year collaboration at a diabetes clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The compliance orientation is evident in many studies conducted on diabetes in Africa. Many researchers in Africa who have conducted studies on adherence (used interchangeably with compliance) found that instructions and treatment goals were usually established with little or no input from patients and assumed that SME and SMS were in place for patients ( Abrahams et al, 2019 ; Adejoh, 2014 ; Watermeyer et al, 2019 ). Unfortunately, this assumption does not seem to be borne out, given the findings of this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The compliance orientation is evident in many studies conducted on diabetes in Africa. Many researchers in Africa who have conducted studies on adherence (used interchangeably with compliance) found that instructions and treatment goals were usually established with little or no input from patients and assumed that SME and SMS were in place for patients ( Abrahams et al, 2019 ; Adejoh, 2014 ; Watermeyer et al, 2019 ). Unfortunately, this assumption does not seem to be borne out, given the findings of this and other studies.…”
Section: Discussionmentioning
confidence: 99%